The Effect of Post and Brennan Strategy in Acquiring Copper Plate Skills for the Students of the Fine Arts - Mahdi Jari, Abbas; Abbood Jaber, Ronak; Muhammad Ali, Hussain ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Due to the significant role that strategies play in producing the arts, the scope of this study is to determine the impact of the Post and Brennan strategy in acquiring copper plate skills among the morning second-grade students of the Fine Arts Institute. To achieve this objective, two hypotheses were utilized in the cognitive and performance-based outcome tests in this study, an experimental approach was employed, using an experimental design for the two equivalent groups, which are the experimental and control groups for both pre- and post-tests. The research included up to 242 students of the fine arts institute. Also included 30 samples of students in the second grade. Plans were formulated for the Post and Brennan strategy as well as the conventional one, building a cognitive test consisting of 25 items and a performance-based test, which consisted of 15 items, to demonstrate the research outcomes. A set of statistical tools was employed. The outcomes have revealed that there are statistical variations at the level of (0.05) among the mean ranks of the experimental group, those who study based on the Post and Brennan strategy and the mean ranks of the control group those who study based on the conventional method in acquiring copper plate skills in both the cognitive and performance post tests. DOI: https://doi.org/10.54633/2333-024-056-024